West vis-à-vis East - Zuocheng, Zhang (Dějiny – teorie – kritika, 2021)
According to XiJinping’s speech at the Symposium on the Work of Philosophy and Social Sciences on May 17th,2 Chinese historiography has been establishing a disciplinary system, academic system, and discourse system with Chinese characteristics since 2016. Disciplinary system construction refers to strengthening the construction of emerging disciplines (e.g., digital history, maritime history etc.) and interdisciplinary disciplines (e.g., environmental history, urban history etc.), as well as strengthening the support of unpopular disciplines with the value of Chinese cultural heritage such as the Oracle research which started with Wang Yirong (1845–1900), Liu E (1857–1909), Luo Zhenyu (1866–1940) and Wang Guowei (1877–1927). Academic system construction includes but is not limited to the construction of Marxist academic research, continuing the development of Marxism in contemporary China and in the 21st century. Discourse system construction means primarily refining the representative concepts and theories which explain Chinese practice and have influence in the international academia. Contemporary Chinese historians know that these three systems are influenced by the West but they should be distinguished from it.